All Days 2018
DOI: 10.2118/193388-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Potential of Combined Controlled Salinity and Bio-Surfactant CSBS in Enhanced Oil Recovery EOR Processes

Abstract: In this study, we investigate potential application of environment-friendly bio-surfactants (EFBS) in EOR processes. We assess the prospect of combining the EFBS with controlled salinity (CS) water injection in optimising oil recovery using rhamnolipid and protein-enzyme as case study. Rock component analysis, bio-surfactant solubility in brine of varied concentration and composition, crude oil-brine interfacial tension (IFT) and bio-surfactants emulsification activity test were carried out as part of the prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The results are consistent with the spontaneous imbibition at similar conditions and indicate the ability of CSB and biosurfactants to shift the wetting state of rock sample towards being more neutral (i.e., initially oil-wet rock samples became less oil-wet when using these solutions). Furthermore, the results of this study show that CSB imbibition increases oil recovery relative to FMB but the process was accompanied by apparently emulsified oil production, which is consistent with the core flooding experiments carried out by Udoh et al [34]. This suggests the possibility of formation of microdispersion of micelles [18] or rock dissolution [45,46] during CSB displacement process.…”
Section: Wettability Alteration: Spontaneous Imbibitionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results are consistent with the spontaneous imbibition at similar conditions and indicate the ability of CSB and biosurfactants to shift the wetting state of rock sample towards being more neutral (i.e., initially oil-wet rock samples became less oil-wet when using these solutions). Furthermore, the results of this study show that CSB imbibition increases oil recovery relative to FMB but the process was accompanied by apparently emulsified oil production, which is consistent with the core flooding experiments carried out by Udoh et al [34]. This suggests the possibility of formation of microdispersion of micelles [18] or rock dissolution [45,46] during CSB displacement process.…”
Section: Wettability Alteration: Spontaneous Imbibitionsupporting
confidence: 90%
“…Also, the use of CSBS-G and CSBS-R increases oil recovery relative to FMB and CSB applications with CSBS-R process being characterised by fastest imbibition rate. This effect is attributable to its high surface activity that enhances oil-brine IFT reduction and increase in capillary effect [34,38].…”
Section: Wettability Alteration: Spontaneous Imbibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenzyme is a water soluble protein-enzyme produced using DNA of selected oil-eating microbes [11,24]. Greenzyme has not been extensively studied, although there are some recent studies (e.g., [13,25]) on its EOR applications but limited studies have been reported on its physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…reservoirs in the Niger Delta and elsewhere (John et al 2019;Elharith et al 2019;Ogolo et al 2018;Olabode et al 2018;Udoh et al 2018;Obinna et al 2016). For simplicity, both the porosity and K v /K h remain unchanged for all the cases investigated.…”
Section: Numerical Modelmentioning
confidence: 99%